Comportamento de ajuda entre os 'bóias-frias': um estudo exploratório - Hamburger, Vesna Ilana (1986)
The objective of this research was to collect manifestations of helping behavior among 'bóias-frias ' by mean s of their own report, with the objective of analyzing the implications of such behavior on their social organization while a specific group. Forty-seven subjects of both sexes were interviewed in their work place. The instrument used was a structured interview developed by this study researcher, consisting of 26 questions. The purpose of these questions was to obtain frequencies, reasons and helping situations, begged or spontaneous , reported by the interviewer in relation to his mates and vice-versa , both inside and outside their work place . It was observed that when inquired whether they give or receive any help, there was a high index of affirmative responses and when they were invited to report them , the index of such responses suffered a remarkable decrease o It was discussed the possible reasons for the occurrence of such an event. The analysis of the helping situations reported served to a better understanding about how the freelance job structure determines the configurations of helping relations among 'bóias-frias' and how much these relations, in turn, influence the social relations of these workers.